An Observational Study on Use of Intravenous Paracetamol for Closure of Patent Ductus Arteriosus in Newborns - Dhungana, Diwas; Shrestha, Manish; Joshi, Suchita (Nepal Mediciti Medical Journal, 2021)
Introduction: Failure or delay in spontaneous closure of ductus arteriosus is commonly seen among very low birth weight and very preterm neonates (<32 weeks), results in patent ductus arteriosus (PDA). Hemodynamically significant PDA (hs-PDA) is associated with significant morbidity and mortality if not timely intervened. At present, treatment modalities for hs- PDA remain pharmacological with nonspecific cyclo-oxygenase inhibitors such as ibuprofen/indomethacin or surgical ligation whenever pharmacological management is contraindicated. Recently, trials with prostaglandin synthase inhibitor, paracetamol are emerging as an effective treatment modality for PDA closure. In this retrospective observational cohort study, we evaluated the effectiveness of intravenous paracetamol as a first line therapy in very low birth weight infants with hemodynamically significant PDA. Methods: Twenty four preterm infants with hemodynamically significant PDA (hs-PDA) were treated with intravenous paracetamol 15mg/kg every 6 hourly and subsequent closure was evaluated clinically and by follow-up 2D-Echocardiography. The dosage of 15 mg/kg for IV paracetamol was chosen based on previously reported data for paracetamol in the treatment of PDA in preterm newborns. Results: PDA closure following intravenous paracetamol was evident in 22 preterm neonates (91.67%). There were no significant side effects noted with paracetamol therapy. Conclusions: This study concludes that intravenous paracetamol is an effective alternative for the pharmacological closure of hemodynamically significant patent ductus arteriosus in preterm infants.